The Study of Seaweed Pond Cultivation (Gracilaria sp.) in West Malangke District, North Luwu Regency - Safrini, Dian; Adhawati, Sri Suro; Cangara, Arie Syahruni; Made, Sutinah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
Gracilaria sp. is the most widely cultivated and traded type of seaweed because it has high economic value and has market prospects both domestically and abroad. This study aims to determine the amount of production costs, income and to determine the dynamics of marketing seaweed (Gracilaria sp.) in West Malangke District, North Luwu Regency. The research was conducted from April to May 2021. This type of research is descriptive using qualitative and quantitative approaches. The sampling method used is purposive sampling with a total sample of 42 people. Sources of data used are primary data and secondary data. Quantitative descriptive data analysis includes economic aspects and marketing aspects. The results showed; the wider the land owned by seaweed cultivators Gracilaria sp. the greater the cost (output) incurred. The average net profit received by cultivators on land <1 ha is Rp. 47,040,000 per year, then on a land of 1-2 Ha earn a profit of Rp. 77,103,158 per year and on an area of ​​2-3 Ha earn a profit of Rp. 147,000,000 per year. Meanwhile, in the marketing aspect, there are two marketing institutions, namely collectors and wholesalers. In the marketing process there are differences in margins, profits and marketing efficiency obtained at each marketing agency for seaweed Gracilaria sp. The highest marketing margin for sales of seaweed Gracilaria sp. found in wholesalers, namely Rp. 2.500,-/Kg. The highest marketing profit is also found in wholesalers, which is Rp. 2,260,859,-/Kg.